An ultra-high resolution pulsed-wire magnet measurement system - D'Audney, Alex, author; Milton, Stephen, advisor; Biedron, Sandra, advisor; Johnson, Thomas, committee member (Colorado State University. Libraries, 2016)
The performance of a Free-Electron Laser (FEL) depends in part on the quality of the magnetic field in the undulator. Ideally the magnetic field on the axis of the undulator is transverse to the axis and sinusoidally varying due to the periodic sequence of alternating field dipole magnets. The resulting ideal trajectory of a relativistic electron bunch traveling along the axis is also sinusoidal in the plane perpendicular to that of the ideal magnetic field. Imperfections in the magnetic field lead to an imperfect electron trajectory, both offset and angle, as well as a relative phase error between the oscillation phase of the electrons and the generated electromagnetic field. The result of such errors is a reduction of laser gain impacting overall FEL performance. A pulsed-wire method can be used to determine the profile of the magnetic field. This is achieved by sending a square-current pulse through a wire placed along the length of the axis that will induce an Lorentz-force interaction with the magnetic field. Measurement of the resulting displacement in the wire over time using a motion detector yields the first or second integrals of the magnetic field and so provides a measure of the local magnetic field strength. Dispersion in the wire can be corrected using algorithms, with a resulting increase in overall accuracy of the measurement. Once the fields are known, magnetic shims can be placed to correct the magnetic fields to the desired level. In this thesis we will describe the design, construction and testing of a pulsed-wire magnetic measurement system and use this system to characterize the CSU FEL undulator.
Keywords: pulsed-wire; magnet characterization; undulator